The impacts of cash flow volatility on Chinese firms: investment, debt maturity, cost of capital - Yu, Zichen (2019)
This thesis attempts to investigate cash flow volatility on Chinese listed firms. It mainly consists of three empirical chapters on the relation between cash flow volatility and Chinese firms' investment, debt maturity, cost of capital.